From Language Learning Media to Representing Turkish Culture: Cultural Content in Turkish Language Textbooks - Mualimin, Mualimin; Fathiyakan, Fathiyakan; Rahayu, Siti (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Language has a close relationship with culture, so that language learning often uses cultural content as a learning medium. Therefore this study aims to analyze the cultural content in textbooks for learning Turkish and its relation as a medium of learning between Turkish languages. This study is qualitative research with a literature study approach. The source of the data in this study was the textbook for learning Turkish, namely